ANALISIS RASIO ROA DAN NPM TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Siti Mudawanah; Nalsal, Pindonta (The Asia Pacific Journal Of Management Studies, 2025)
This study aims to analyze the effect of Return on Assets (ROA) and Net Profit Margin (NPM) on stock prices of food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) during 2022–2023. The population consists of 95 food and beverage subsector companies. Using purposive sampling, 83 companies were initially selected. However, after outlier testing, 43 companies were excluded, leaving a final sample of 40 companies (80 observations) for data analysis. The research applies a quantitative approach with multiple linear regression analysis. Descriptive statistics reveal considerable variation in profitability levels among companies. Regression results show that ROA has no significant effect on stock prices, while NPM exhibits a positive and significant effect. Simultaneously, ROA and NPM significantly influence stock prices, although their contribution is relatively small (R² = 7.5%). These findings suggest that stock prices in the food and beverage subsector are not solely determined by profitability ratios, but are also influenced by external factors such as macroeconomic conditions and market sentiment. This study provides a theoretical contribution by enriching the literature on fundamental stock analysis and practical implications for investors in making investment decisions based on corporate financial performance.